Preparation and characterization of carbon molecular sieve produced from palm shell - Wong, Kwon Cheong (2006)
Various types of microporous carbon gas adsorbents have been prepared from Malaysia carbonaceous solid waste, the palm shell as the precursor for further modification into carbon molecular sieve (CMS). It is an advantage to utilize the palm shell as starting material by converting into useful CMS since it can be obtained easily and abundantly in the country. The precursors were prepared in laboratory fluidized and fixed bed reactors by one-step physical treatments, which included carbonization in N2 flow and directly followed by CO2 activation. The effects of carbonization parameters, such as carbonization temperature, hold time and N2 flow rate on the porosity development have been studied. The characterizations of precursors were carried out by constant volumetric physisorption analyzer to determine various characteristic parameters from the analysis of adsorption isotherm. Here, N2 and CO2 have been used as the adsorptive gas for analysis at 77 and 273 K, respectively. Although the entire precursor appeared to be highly microporous, only some precursors produced were considered suitable to be used as precursor of CMS for O2/N2 separation based on the literature survey finding. Then the precursors were modified into CMS using chemical vapor deposition (CVD) technique. The CVD technique involved deposition of pyrolytic carbon on the precursor by cracking of hydrocarbon gas substance. CVD parameters such as type of hydrocarbon gas substance, deposition temperature, deposition hold time and % v/v of hydrocarbon gas substance were manipulated to have pyrolytic carbon deposited on the pore mouth for improving separation selectivity with some trade-off in O2 adsorption capacity. The characterizations of CMS were carried out by constant volumetric physisorption analyzer to determine the adsorption kinetic of O2 and N2 for determining the selectivity and O2 adsorption capacity from isotherm at 298 K. The deposition mechanisms were proposed from the result obtained. By directly applied CVD to deposit carbon on precursor for modifying the pore mouth produced CMS which is not up to expected performance compared to commercial carbon molecular sieve (CCMS). It was due to the existence of a small portion of pore with bigger pore size. These pores could not be effectively lowered because further deposition of the pyrolytic carbon will close the smaller pore resulting in abrupt reduction in O2 adsorption capacity. The conventional CVD involving pore blocking by pyrolytic carbon followed by control gasification in CO2 atmosphere were used. In this experiment, the best samples from directly applied CVD and conventional CVD have selectivity of 8.00 and 5.00 respectively compared to the selectivity of 2.09 for the precursor.